Mestizaje gráfico en Colombia entre 1900 y 1930. El diseño gráfico y la construcción de una imagen de nación moderna y civilizada - Daniel Plata Becerra; Mauricio Antonio Hoyos; Marcela Arias (Nuevo mundo - Mundos Nuevos, 2022)
This paper is part of the conclusions of a research aimed to identify the origins and conditions of production of visual brands in Colombia in the first three decades of the XX century. Following the consolidation and analysis of the image corpus we identified several trends, which were established and developed during the research period, being the “graphic mixing” the one more closely related to the circulation of people, practices, ideas and goods. To deconstruct these phenomena, we engage it in three parts: the reasons behind the use of European visual codes, the way in which these codes were introduced in the country’s visual language, and the stages leading to the “graphic crossbreeding”.